2013
DOI: 10.5142/jgr.2013.37.371
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS-based metabolomic analysis of serum and livers from red ginseng-fed rats

Abstract: Serum and liver metabolites in rats fed red ginseng (RG) were analyzed by ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry. The mass data were analyzed by partial least squares-discriminant analysis (PLS-DA) to discriminate between control and RG groups and identify metabolites contributing to this discrimination. The RG group was clearly separated from the control group on PLS-DA scores plot for serum samples, but not liver samples. The major metabolites contributing to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
(26 reference statements)
1
22
0
Order By: Relevance
“…In particular, metabolomics studies demonstrated that branched-chain amino acids, short-chain dicarboxylacylcarnitine species, and trimethylamine N-oxide were strongly associated with cardiovascular risks [8]. Moreover, metabolomics studies on ginseng intake revealed that a decrease in blood lysophosphatidylcholine (LPC) levels in patients with prehypertension [5] and rats [11] might reduce blood pressure. Moreover, epidemiological data have indicated that estrogen hormone levels are strongly related to the progression of cardiovascular diseases [12]; however, the specific ginseng intake-induced changes in metabolite profiles, including any changes to steroid hormones with atheroprotective effects, have not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, metabolomics studies demonstrated that branched-chain amino acids, short-chain dicarboxylacylcarnitine species, and trimethylamine N-oxide were strongly associated with cardiovascular risks [8]. Moreover, metabolomics studies on ginseng intake revealed that a decrease in blood lysophosphatidylcholine (LPC) levels in patients with prehypertension [5] and rats [11] might reduce blood pressure. Moreover, epidemiological data have indicated that estrogen hormone levels are strongly related to the progression of cardiovascular diseases [12]; however, the specific ginseng intake-induced changes in metabolite profiles, including any changes to steroid hormones with atheroprotective effects, have not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Serum and liver metabolites in rats fed with red ginseng are analysed by UPLC‐Q‐TOF‐MS combined with PLS‐DA to discriminate between control and red ginseng and identify biomarker metabolites. The results suggest long‐term red ginseng might relieve stress and prevent physiological and biological problems . The anti‐diabetic effect of water‐soluble ginseng polysaccharide has also been reported in recent years .…”
Section: Metabonomic Studies Of Ginseng Intervention Effects Based Onmentioning
confidence: 70%
“…Unlike urine, blood samples contain higher protein and lipid contents, which along with narrow signals of small molecules produce broader signals in NMR spectra. Different spectral editing methods are used to deal with specific small and large signals in NMR spectra (Tang et al 2004), whereas sample pretreatments such as derivatization and protein precipitation are performed before the anlaysis of serum samples on GC-and LC-MS, respectively (Dettmer et al 2007;Kim et al 2013).…”
Section: Analytical Tools For Metabolite Profilingmentioning
confidence: 99%